Treatment Outcomes after Breast Conserving Therapy in Breast Cancer Patients in Faculty of Medicine, Vajira Hospital: a 10-Year Retrospective Study - Rongsriyam, Kanisa; Sueangamiam, Kamonrat; Tantivatana, Thanatip (Vajira Medical Journal : Journal of Urban Medicine, 2022)
Objective: To study the 5 and 10-year survival rate and prognosis factors in breast cancer patients receiving breast conservative treatment (BCT). Methods: A retrospective descriptive analysis of BCT patients who were treated in Radiation Oncology unit, Department of Radiology, Faculty of Medicine Vajira Hospital between 2009 and 2019. The Kaplan-Meier method was used for survival analysis. The authors analyzed association of patients and tumor characteristics with survival using the log-rank test and Cox models. Results: A total of 158 BCT patients were included. Five-year overall and disease-free survivals were 100% and 97.8%, respectively, with 10-year overall survival and disease-free survival were 100% and 95.7%, respectively. Numbers of positive nodes more than 4 (HR of 10.25; 95% CI:1.66-63.18) are significantly prognostic factors related to recurrence. Conclusions: Breast cancer patients who were treated with BCT had a favorable long-term survival outcome. Survival rates did not change much between 5 and 10 years. The important prognostic factor affecting disease-free survival was axillary lymph node metastasis.